Formamide Catalysis Facilitates the Transformation of Aldehydes into Geminal Dichlorides - Huy, Peter Helmut (Synthesis, 2019)
Herein, a novel method for the transformation of aldehydes into geminal dichlorides based on phthaloyl chloride as reagent and N-formylpyrrolidine as Lewis base catalyst is disclosed. Given the mild reaction conditions, the current protocol is distinguished by high levels of functional group compatibility and scalability and is operationally simple. The in situ formation of a Vilsmeier Haack reagent type intermediate is likely to be essential for this organocatalytic nucleophilic substitution reaction.
Keywords: homogeneous catalysis; nucleophilic substitutions; Lewis base catalysis; halogenation; organocatalysis; geminal dihalogenides; Vilsmeier Haack reagent